A polyphenol-assisted IL-10 mRNA delivery system for ulcerative colitis - Zhejie Chen; Wei Hao; Caifang Gao; Yangyang Zhou; Chen Zhang; Jinming Zhang; Ruibing Wang; Yitao Wang; Shengpeng Wang (Elsevier, 2022)
With the development of synthesis technology, modified messenger RNA (mRNA) has emerged as a novel category of therapeutic agents for a broad of diseases. However, effective intracellular delivery of mRNA remains challenging, especially for its sensitivity to enzymatic degradation. Here, we propose a polyphenol-assisted handy delivery strategy for efficient in vivo delivery of IL-10 mRNA. IL-10 mRNA binds to polyphenol ellagic acid through supramolecular binding to yield a negatively charged core, followed by complexing with linear polyetherimide and coating with bilirubin-modified hyaluronic acid to obtain a layer-by-layer nanostructure. The nanostructure specifically up-regulated the level of IL-10, effectively inhibited the expression of inflammatory factors, promoted mucosal repair, protected colonic epithelial cells against apoptosis, and exerted potent therapeutic efficacy in dextran sulfate sodium salt-induced acute and chronic murine models of colitis. The designed delivery system without systemic toxicity has the potential to facilitate the development of a promising platform for mRNA delivery in ulcerative colitis treatment.